2003
DOI: 10.1590/s0044-59672003000400016
|View full text |Cite
|
Sign up to set email alerts
|

Duração do ciclo de vida de Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae: Leptysminae) e aspectos de seu comportamento alimentar na Amazônia central

Abstract: O gafanhoto Cornops aquaticum (Bruner, 1906) (Orthoptera: Acrididae: Leptysminae) completa seu ciclo de vida em Eichhornia (Pontederiaceae). Em experimentos ao ar livre, durante o período da enchente, foi verificado que a cópula pode durar entre 40 a 120 minutos. Cada postura tem em média 13,4 ovos (+/- 3,2) e o período de incubação durou 34,1 dias (+/- 1,97). A duração média do desenvolvimento de ovo a adulto foi de 156,2 dias, sendo 34,1 do estágio de ovo, 53,4 do estágio ninfal e 68,7 do estágio adulto. Ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…The species lives in close association with Pontederiaceae floating meadows, especially the genus Eichhornia Kunth (1842) (Center et al 2002). The water hyacinth is the most typical macrophyte of floating meadows in large rivers in South America (Blanco Belmonte et al 1998) and is considered the worst pest of natural and artificial water bodies in tropical latitudes around the world (Waterhouse & Norris 1987;Julien et al 2001;Center et al 2002).Cornops aquaticum is being considered in South Africa as a biological control agent of the water hyacinth, E. crassipes (Bownes et al 2010a(Bownes et al , 2010b because laboratory and field studies on C. aquaticum have demonstrated a high host plant specificity to E. azurea and E. crassipes (Zolessi 1956;Silveira Guido & Perkins 1975;Cordo 1999;Hill & Oberholzer 2000;Ferreira & Vasconcellos-Neto 2001;Oberholzer & Hill 2001;Adis & Junk 2003;Vieira & Santos 2003;Lhano et al 2005;Franceschini et al 2011). Franceschini et al (2007Franceschini et al ( , 2008 showed that populations of C. aquaticum in North-eastern Argentina, in two wetlands with different host plants and *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The species lives in close association with Pontederiaceae floating meadows, especially the genus Eichhornia Kunth (1842) (Center et al 2002). The water hyacinth is the most typical macrophyte of floating meadows in large rivers in South America (Blanco Belmonte et al 1998) and is considered the worst pest of natural and artificial water bodies in tropical latitudes around the world (Waterhouse & Norris 1987;Julien et al 2001;Center et al 2002).Cornops aquaticum is being considered in South Africa as a biological control agent of the water hyacinth, E. crassipes (Bownes et al 2010a(Bownes et al , 2010b because laboratory and field studies on C. aquaticum have demonstrated a high host plant specificity to E. azurea and E. crassipes (Zolessi 1956;Silveira Guido & Perkins 1975;Cordo 1999;Hill & Oberholzer 2000;Ferreira & Vasconcellos-Neto 2001;Oberholzer & Hill 2001;Adis & Junk 2003;Vieira & Santos 2003;Lhano et al 2005;Franceschini et al 2011). Franceschini et al (2007Franceschini et al ( , 2008 showed that populations of C. aquaticum in North-eastern Argentina, in two wetlands with different host plants and *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Tal resultado foi evidente para os adultos e imaturos testados (Tabelas 1 e 2). Ressalta-se que a aceitação de E. crassipes por C. aquaticum já foi obtida em outros estudos realizados com esse gafanhoto semiaquático (Adis & Junk, 2003;Vieira & Santos, 2003;Lhano et al, 2005;Capello et al, 2011;Franceschini et al, 2011), entretanto deve-se considerar que essa macrófita aquática pertence à família Pontederiaceae, a qual reúne os gêneros Pontederia e Eichhornia, que são considerados hospedeiros naturais de C. aquaticum (Zolessi, 1956;Roberts & Carbonell, 1979;Guido & Perkins, 1975;Hill & Oberholzer, 2000).…”
Section: Resultsunclassified
“…Quanto à aceitação de Pistia stratiotes, vale ressaltar que essa espécie também foi aceita como alimentação por C. aquaticum em outro estudo na região amazônica (Vieira & Santos, 2003), todavia, estudos realizados na Argentina por Capello et al (2012) indicaram que esta macrófita aquática não faz parte da dieta alimentar do gafanhoto naquela região. Já em relação à aceitação da Macrófitas aquáticas N Número de dias de experimento Esse resultado parece indicar que o gafanhoto em estado de ausência de alimento específico (com fome) tende a comer outras plantas, buscando saciar a falta de comida ou consumindo-as como fonte alimentar alternativa temporária.…”
Section: Resultsunclassified
“…The host specificity of C. aquaticum has been extensively studied, using field assessment and traditional laboratory‐based no‐choice and choice trials in the region of introduction (Hill & Oberholzer, 2000; Oberholzer & Hill, 2001), and the region of origin (Ferreira & Vasconcellos‐Neto, 2001; Vieira & Santos, 2003; Lhano et al, 2005; Capello et al, 2011). The results of these studies have been fairly consistent and have shown that C. aquaticum is an oligophagous insect on the genus Pontederia , mainly P. crassipes and P. azurea .…”
Section: Discussionmentioning
confidence: 99%
“…In its native range, C. aquaticum is closely associated with the host plants Pontederia spp., particularly P. crassipes , which support the insect through its entire life cycle (Ferreira & Vasconcellos‐Neto, 2001; Adis & Junk, 2003; Colombo et al, 2021). Total development of C. aquaticum from nymphs to adults takes 317 days in males and 288 days in females in the subtropics (Franceschini, 2008; Capello & Franceschini, 2014), but it can take only 122 days in the tropics (Vieira & Santos, 2003). The timeframe of the immature life stages reaches up to 81 days, and adult longevity up to 264 days (Adis et al, 2004; Franceschini, 2008; Capello & Franceschini, 2014).…”
Section: Introductionmentioning
confidence: 99%